Faktor Lingkungan Belajar Sebagai Fenomena Sosial Anak Dalam Pembelajaran Kelas IV SDN 3 Blimbingrejo - Ndorotul Ainy, Fadya; Putri Cahyani; Innes Annisa’ Istiqomah; Nur Fajrie (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This research is a descriptive qualitative research in the form of descriptions from the results of interviews and documentation studies that aim to determine learning environmental factors as a social phenomenon for children in learning in class IV SD N 3 Blimbingrejo. The population in the study were all fourth grade students at SD N 3 Blimbingrejo, totaling 19 students. Sampling in this study used saturated sampling so that the sample taken was 19 students. Research data obtained by collecting data in the form of interviews, questionnaires and documents. From the results of the study there was a significant relationship between learning environment factors and children's social phenomena in the learning of fourth graders at SD N 3 Blimbingrejo.